1816 La. Acts 92, An Act to Amend the Act Entitled “An Act to Incorporate the city of New Orleans” and the Act Entitled “An act to determine the mode of election of the mayor, recorder and other public officers necessary for the administartion and police of the city of New Orleans and for Other Purposes [sic], § 1. - (:unkn) unknown (General Publisher, 1816)
[T]he mayor and city council of the city of New Orleans shall have full power and authority . . . [T]o prevent gun powder being stowed within the walls and suburbs in such quantity as to endanger the public safety .
--
Keywords: GUN POWDER STORAGE